[Pumping insecticide into aircraft] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Insecticide being pumped into the plane just before takeoff to spray the sugarcane fields.
Cataloger's title
Keywords: Airplanes; Sugar crops -- Trinidad and Tobago; Caroni (1975) Limited